Epidemic of Mungbean Yellow Mosaic Virus (MYMV) Disease of Soybean: A Potential Threat in Changing Weather under Agro-climatic Conditions of Jabalpur, Madhya Pradesh - Silodia, Kunika; Bhale, Usha; Bhale, M. S. (International Journal of Bio-resource and Stress Management, 2017)
In all 11 major diseases were observed at VC-V3, R1-R3 and R5-R6 stage at pre-selected farmer’s field of 8 villages covering 24 locations employing fixed plot monitoring method. An epidemic of MYMV was experienced which had never been major disease problem- threat under Jabalpur......